A mixture of innate cryoprotectants is key for freeze tolerance and cryopreservation of a drosophilid fly larva - Kučera, Lukáš; Moos, Martin; Štětina, Tomáš; Korbelová, Jaroslava; Vodrážka, Petr; Des Marteaux, Lauren; Grgac, Robert; Hůla, Petr; Rozsypal, Jan; Faltus, Miloš; Šimek, Petr; Sedlacek, Radislav; et al. (The Journal of experimental biology, 2022)
Insects that naturally tolerate internal freezing produce complex mixtures of multiple cryoprotectants (CPs). Better knowledge on composition of these mixtures, and on the mechanisms of individual CP interactions, could inspire development of laboratory CP formulations optimized for cryopreservation of cells and other biological material. Here, we identify and quantify (using high resolution mass spectrometry) a range of putative CPs in larval tissues of a subarctic fly, Chymomyza costata, which survives long-term cryopreservation in liquid nitrogen. The CPs proline, trehalose, glutamine, asparagine, glycine betaine, glycerophosphoethanolamine, glycerophosphocholine and sarcosine accumulate in hemolymph in a ratio of 313:108:55:26:6:4:2.9:0.5 mmol l-1. Using calorimetry, we show that artificial mixtures, mimicking the concentrations of major CPs in hemolymph of freeze-tolerant larvae, suppress the melting point of water and significantly reduce the ice fraction. We demonstrate in a bioassay that mixtures of CPs administered through the diet act synergistically rather than additively to enable cryopreservation of otherwise freeze-sensitive larvae. Using matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI), we show that during slow extracellular freezing trehalose becomes concentrated in partially dehydrated hemolymph where it stimulates transition to the amorphous glass phase. In contrast, proline moves to the boundary between extracellular ice and dehydrated hemolymph and tissues where it probably forms a layer of dense viscoelastic liquid. We propose that amorphous glass and viscoelastic liquids may protect macromolecules and cells from thermomechanical shocks associated with freezing and transfer into and out of liquid nitrogen.
Keywords: kryoprotektivní látky; Freezing; trehalosa; Metabolites; Ice; Natural deep eutectic systems; Cryopreservation; Nitrogen; Proline; prolin; Trehalose; Freeze tolerance; zmrazování; larva; Animals; Cryoprotective Agents; zvířata; dusík; led; Larva; kryoprezervace; Cryoprotection; Insects